High-temperature-resistant anti-corrosion electrode slurry and preparation method thereof
By developing a high-temperature corrosion-resistant electrode slurry containing Ag/Pd powder and Al-Sm-Si-Ca-Mg system high-temperature corrosion-resistant electrode powder, the problem of signal instability and insufficient reliability of automotive oxygen sensors in high temperature environments is solved, and good co-fired and signal stability with the alumina-based insulating layer at high temperature is achieved.
Patent Information
- Application Number
- CN202411711506.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
AI Technical Summary
When the automotive oxygen sensor works in a high-temperature corrosive environment, the high-temperature output signal is unstable and the reliability of long-term working cannot be guaranteed.
A high-temperature corrosion-resistant electrode slurry is developed, including Ag/Pd powder, Al-Sm-Si-Ca-Mg system high-temperature glass-ceramic phase powder and organic carrier, which can achieve good wetting and co-firing with the alumina-based insulating layer.
The electrode slurry is well co-fired with the alumina-based insulating layer above 1200°C, ensuring that the oxygen sensor can output signals stably in a high temperature environment, reducing the risks of lead poisoning, silicon poisoning and thermal poisoning.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic materials, and in particular to a high temperature resistant and corrosion resistant electrode slurry and a preparation method thereof. Background Art
[0002] Automotive oxygen sensors are usually installed in the exhaust system of cars and are directly exposed to the exhaust gas produced after engine combustion. Exhaust gas contains not only normal combustion products such as oxygen, nitrogen, and carbon dioxide, but also some pollutants and corrosive gases, such as sulfides, nitrogen oxides, water vapor, and incompletely burned hydrocarbons. These gases will corrode the oxygen sensor, greatly shorten its service life, and thus affect its reliability and stability. The working environment of automotive oxygen sensors is very harsh, and they work at high temperatures of 300°C to 850°C for a long time. In addition, water vapor in the exhaust gas will condense into water under low temperature conditions. If the sealing of the oxygen sensor is not good, water will enter the sensor and corrode the internal electrode, which will cause short circuits and other faults, causing the sensor to fail to work. For this reason, high requirements are placed on the electrode material for the sensor, requiring it to be resistant to high temperature and corrosion, and have good bonding strength and excellent airtightness with the aluminum oxide insulation layer to ensure that it can work stably and reliably in harsh working environments.
[0003] Glass is an inorganic non-metallic material with strong corrosion resistance and is not easy to age. Good adhesion allows Ag / Pd slurry with glass material as filler to form a dense molten glass ceramic film layer on the surface of the alumina insulation layer, while also reducing the chances of lead poisoning, silicon poisoning and heat poisoning of the oxygen sensor. For example, the Al-La-Si-Ca-Mg based glass system has a high softening point, and after microcrystallization, its temperature resistance is greatly improved, and it can work well and stably at 850°C.
[0004] Therefore, developing a high-temperature anti-corrosion electrode slurry that can achieve good wetting and co-firing with the alumina-based insulating layer is an urgent problem to be solved. Summary of the invention
[0005] In view of this, the present invention provides a high-temperature resistant and anti-corrosion electrode slurry and a preparation method thereof, and provides a high-temperature anti-corrosion electrode slurry that can achieve good infiltration and co-firing with an alumina-based insulating layer, so as to solve the technical problem that when the oxygen sensor in the current automotive exhaust system works under high-temperature corrosive conditions, the high-temperature output signal of the sensor is unstable and the long-term working reliability cannot be guaranteed.
[0006] On the one hand, the present invention provides a high temperature resistant and anti-corrosion electrode slurry, which comprises, by mass percentage, 45-77% of Ag / Pd powder, 3-15% of glass ceramic phase powder, and 15-20% of an organic carrier; wherein the glass ceramic phase powder is a high temperature resistant glass powder of an Al-Sm-Si-Ca-Mg system;
[0007] The glass ceramic phase powder includes, by mass percentage, one or more of: Al2O3 20-45%, MgO 15-25%, SiO2 10-15%, CaO 5-15%, ZnO 1-5%, Na2O / BeO 0.5-3%, Y2O3 0.5-5%, Sm2O3 / SrO 5-10%, MgF / ZrO2 0.5-5%, mullite powder 0.1-05%, and / or La2O3 0-2%, BeO 0-2%, BaO 0-2%, MnO2 0-2%, CuO 0-2%, K2O 0-2%, V2O5 0-2%, Li2O 0-2% / Gd2O3 0-2%.
[0008] The mass ratio of MgF to ZrO2 in the MgF / ZrO2 is 3:7, the mass ratio of Na2O to BeO in Na2O / BeO is 2:1, and the mass ratio of Sm2O3 to SrO in Sm2O3 / SrO is 1:4.
[0009] The present invention also provides a method for preparing the high temperature resistant and corrosion resistant electrode slurry, comprising:
[0010] Step 1: Weigh the components of the glass ceramic phase powder according to the mass percentage and mix them evenly; according to the mass percentage, the components include: Al2O3 20-45%, MgO 15-25%, SiO2 10-15%, CaO 5-15%, ZnO 1-5%, Na2O / BeO 0.5-3%, Y2O3 0.5-5%, Sm2O3 / SrO 5-10%, MgF / ZrO2 0.5-5%, mullite powder 0.1-05%, and / or La2O3 0-2%, BeO 0-2%, BaO 0-2%, MnO2 0-2%, CuO 0-2%, K2O 0-2%, V2O5 0-2%, Li2O 0-2% / Gd2O3 0-2%;
[0011] Step 2: Melting the uniformly mixed glass ceramic phase powder to obtain melted glass liquid;
[0012] Step 3: The molten glass liquid is taken out, and subjected to water quenching, drying, ball milling, and sieving in sequence to obtain Al-Sm-Si-Ca-Mg system high temperature resistant glass powder;
[0013] Step 4: Mix the Al-Sm-Si-Ca-Mg system high temperature resistant glass powder with Ag / Pd powder and an organic carrier to obtain a high temperature resistant and corrosion resistant electrode slurry, wherein the organic carrier includes a binder, a solvent and a dispersant.
[0014] Preferably, the melting in step 2 comprises: heating the uniformly mixed glass-ceramic phase powder to 260-360° C. at a heating rate of 2° C. / min and keeping the temperature for 0.5-2 hours, and then heating the temperature to 1400-1650° C. at a heating rate of 3-5° C. / min and keeping the temperature for 1-2.5 hours to fully melt the glass and obtain melted glass liquid;
[0015] Preferably, the mixing is carried out by ball milling, agate balls are selected as the grinding medium, and the solid content of the mixture is 50-70%.
[0016] Preferably, the binder in step 4 is one or more of epoxy resin, silicone epoxy resin, and polyacrylate, the solvent is one or more of dimethyl phthalate and terpineol; and the dispersant is one or both of methyl pyrrolidone and butanediol.
[0017] The present invention provides a high temperature resistant and anti-corrosion electrode slurry and a preparation method thereof, wherein an Al-Sm-Si-Ca-Mg system high temperature resistant and anti-corrosion microcrystalline glass powder material is used as a filler, and is prepared into an electrode slurry together with Ag / Pd powder, a binder and a solvent. Due to the introduction of the microcrystalline glass powder material into the slurry, it has strong corrosion resistance and good adhesion. The electrode slurry can form a dense molten glass ceramic film layer on the surface of the alumina insulating layer, and can also reduce the probability of lead poisoning, silicon poisoning and heat poisoning of the oxygen sensor. At the same time, the Al-Sm-Si-Ca-Mg basic glass system has a high softening point, and after microcrystallization, the temperature resistance is greatly improved, and it can work well and stably at 850°C.
[0018] The electrode slurry obtained by this method is resistant to high temperature and corrosion, and can be well co-fired with the alumina-based insulating layer at above 1200°C, ensuring that the oxygen sensor can output stable signals under high temperature and harsh environments.
[0019] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. DETAILED DESCRIPTION
[0020] The present invention is further explained below in conjunction with specific implementation schemes, but it is not intended to limit the protection scope of the present invention.
[0021] In order to solve the technical problem that when the oxygen sensor in the current vehicle exhaust system works under high-temperature corrosive conditions, the high-temperature output signal of the sensor is unstable and the long-term working reliability cannot be guaranteed, a high-temperature anti-corrosion electrode slurry that can achieve good infiltration and co-firing with an alumina-based insulating layer and a preparation method thereof are provided.
[0022] According to the percentage by mass, a high temperature resistant and anti-corrosion electrode slurry comprises: 45-75% Ag / Pd powder, 3-15% glass ceramic phase powder, 10-35% organic carrier, wherein the specific components of the glass ceramic phase powder are as follows by mass: 20-45% Al2O3, 15-25% MgO, 10-15% SiO2, 5-15% CaO, 1-5% ZnO, 0.5-3% Na2O / BeO, 0.5-5% Y2O3, 5-10% Sm2O3 / SrO, 0.5-5% MgF / ZrO2, and 0.1-05% mullite powder. The mass ratio of MgF to ZrO2 in MgF / ZrO2 is 3:7, the mass ratio of Na2O to BeO in Na2O / BeO is 2:1, and the mass ratio of Sm2O3 to SrO in Sm2O3 / SrO is 1:4. In addition, the high temperature resistant and anti-corrosion electrode slurry of the present invention may further be added with one or two or more of the following mass percentages of La2O3, BaO, MnO2, CuO, K2O, V2O5, Li2O or Gd2O3. Among them, La2O3 is 0-2%, BeO is 0-2%, BaO is 0-2%, MnO2 is 0-2%, CuO is 0-2%, K2O is 0-2%, V2O5 is 0-2%, Li2O is 0-2% or Gd2O3 is 0-2%.
[0023] Weigh the above components according to mass percentage and mix them evenly.
[0024] The glass ceramic phase powder composition as the functional filler is weighed and mixed uniformly according to the proportion, and then put into a platinum crucible, and kept warm for 0.5-2 hours at a heating rate of 2°C / min to 260-360°C; the temperature is continued to rise to 1400-1650°C at a heating rate of 3-5°C / min, and the crucible is covered to prevent the volatilization of MgF2, and kept warm for 1-2.5 hours to fully melt the glass. The molten glass liquid is taken out for water quenching, drying, ball milling, and sieving 80 meshes to obtain Al-Sm-Si-Ca-Mg system high temperature resistant glass powder. The above glass powder is heated to 900-960°C at a speed of 5-7°C / min, and kept warm for 2-2.5 hours, and the glass powder is microcrystallized, and the sample is cooled with the furnace to obtain Al-La-Si-Ca-Mg system high temperature resistant and corrosion resistant microcrystalline glass powder material.
[0025] In the present invention, SiO2 is a glass network former, and Al2O3 and ZnO are glass network modifier oxides. MgF and ZrO2 are required oxides as mixed nucleating agents. At the same time, in order to control the crystallization phase, a small amount of mullite powder is introduced to promote the growth of the mullite phase. Na2O and BeO are introduced as mixed oxides of alkali metals and alkaline earth metals, which play the role of high-temperature fluxing, accelerating glass melting, and adjusting the glass expansion coefficient; the introduction of CaO has the function of cutting off the regular tetrahedral network structure formed by silica molecules, and reacts with other oxides during high temperature to promote the dissolution of other metal oxides, thereby accelerating the formation of glass. In addition, in the present invention, the glass system also plays a role in absorbing moisture, carbon dioxide and other substances in the glass, reducing voids and defects in the glass, and further improving corrosion resistance in subsequent applications. Y2O3, Sm2O3, SrO, La2O3, BaO, MnO2, CuO, K2O, V2O5, Li2O or Gd2O3 are regulators of glass properties and play a very important role in glass components. They can adjust the viscosity and melting temperature of the glass and improve the mechanical strength of the glass.
[0026] 2) The Al-Sm-Si-Ca-Mg system high temperature resistant and corrosion resistant microcrystalline glass powder prepared above is uniformly mixed with Ag / Pd powder, a binder and a solvent, and the mixing is carried out by ball milling, and agate balls are selected as grinding media. The solid content is controlled at 50-70%, the binder is selected from one or more of epoxy resin, silicone epoxy resin, and polyacrylate, the solvent is one or more of dimethyl phthalate and pinene alcohol, and the dispersant is selected from one or both of methyl pyrrolidone and butanediol.
[0027] The present invention is further explained below in conjunction with specific embodiments.
[0028] Example 1
[0029] A high temperature resistant and anti-corrosion electrode slurry is mainly composed of Ag / Pd powder, high temperature resistant microcrystalline glass powder, and organic carrier, with a solid content of 65%. Ag / Pd powder is 55%, high temperature resistant microcrystalline glass powder is 10%, and the balance is 35% organic carrier. The specific components of the glass ceramic phase powder are as follows by mass %: Al2O3 45%, MgO 25%, SiO2 15%, CaO 10%, ZnO 1.5%, Na2O / BeO 1%, Y2O3 0.5%, Sm2O3 / SrO 0.5%, MgF / ZrO 2 0.5%, mullite powder 0.5%, and MnO2 0.5%. The mass ratio of MgF to ZrO2 in MgF / ZrO2 is 3:7, the mass ratio of Na2O to BeO in Na2O / BeO is 2:1, and the mass ratio of Sm2O3 to SrO in Sm2O3 / SrO is 1:4. The method for preparing the above-mentioned high temperature resistant and anti-corrosion electrode slurry comprises the following steps:
[0030] Weigh each component in the above glass-ceramic formula according to mass percentage and mix them evenly.
[0031] The glass ceramic phase powder composition as the functional filler is weighed and mixed evenly according to the proportion, and then put into a platinum crucible, and kept warm for 2 hours at a heating rate of 2°C / min to 360°C; continue to heat up to 1600°C at a heating rate of 5°C / min, cover the crucible to prevent the volatilization of MgF2, and keep warm for 2 hours to fully melt the glass. The molten glass liquid is taken out for water quenching, drying, ball milling, and sieving 80 mesh to obtain Al-Sm-Si-Ca-Mg system high temperature resistant glass powder. The above glass powder is heated to 920°C at a speed of 5-7°C / min and kept warm for 2.5 hours. The glass powder is microcrystallized and the sample is cooled with the furnace to obtain Al-Sm-Si-Ca-Mg system high temperature resistant and corrosion resistant microcrystalline glass powder material.
[0032] The Al-Sm-Si-Ca-Mg system high temperature resistant and corrosion resistant microcrystalline glass powder prepared above is uniformly mixed with Ag / Pd powder, a binder, a solvent and a dispersant, and the mixing is carried out by ball milling, and agate balls are used as grinding media. The solid content is controlled at 65%, the binder is silicone epoxy resin, the solvent is dimethyl phthalate, and the dispersant is methyl pyrrolidone.
[0033] Example 2
[0034] A high temperature resistant and anti-corrosion electrode slurry is mainly composed of Ag / Pd powder, high temperature resistant microcrystalline glass powder, and organic carrier, with a solid content of 60%. Ag / Pd powder is 52%, high temperature resistant microcrystalline glass powder is 8%, and the balance is 40% of organic carrier. The specific components of the glass ceramic phase powder are as follows by mass %: Al2O3 40%, MgO 25%, SiO2 20%, CaO 10%, ZnO 1.5%, Na2O / BeO 1%, Y2O3 0.5%, Sm2O3 / SrO 0.5%, MgF / ZrO 2 0.5%, mullite powder 0.5%, V2O5 0.5%. The mass ratio of MgF to ZrO2 in MgF / ZrO2 is 3:7, the mass ratio of Na2O to BeO in Na2O / BeO is 2:1, and the mass ratio of Sm2O3 to SrO in Sm2O3 / SrO is 1:4. The method for preparing the above-mentioned high temperature resistant and anti-corrosion electrode slurry comprises the following steps:
[0035] Weigh each component in the above glass-ceramic formula according to mass percentage and mix them evenly.
[0036] The glass ceramic phase powder composition as the functional filler is weighed and mixed evenly according to the proportion, and then put into a platinum crucible, and kept warm for 2 hours at a heating rate of 2°C / min to 350°C; the heating rate is continued to rise to 1590°C at a heating rate of 5°C / min, and the crucible is covered to prevent the volatilization of MgF2, and kept warm for 2 hours to fully melt the glass. The molten glass liquid is taken out for water quenching, drying, ball milling, and sieving 80 mesh to obtain Al-Sm-Si-Ca-Mg system high temperature resistant glass powder. The above glass powder is heated to 900°C at a speed of 5-7°C / min and kept warm for 2.5 hours, and the glass powder is microcrystallized, and the sample is cooled with the furnace to obtain Al-La-Si-Ca-Mg system high temperature resistant and corrosion resistant microcrystalline glass powder material.
[0037] The Al-Sm-Si-Ca-Mg system high temperature resistant and corrosion resistant microcrystalline glass powder prepared above is uniformly mixed with Ag / Pd powder, a binder, a solvent and a dispersant, and the mixing is carried out by ball milling, and agate balls are used as grinding media. The solid content is controlled at 60%, the binder is polyacrylate, the solvent is pine alcohol, and the dispersant is methyl pyrrolidone.
[0038] Those skilled in the art will readily appreciate other embodiments of the present invention after considering the specification and practicing the invention disclosed herein. This application is intended to cover any variations, uses or adaptations of the present invention that follow the general principles of the present invention and include common knowledge or customary techniques in the art that are not disclosed by the present invention. The specification and examples are to be considered exemplary only, and the true scope and spirit of the present invention are indicated by the following claims.
[0039] It should be understood that the present invention is not limited to what has been described above and that various modifications and changes may be made without departing from its scope. The scope of the present invention is limited only by the appended claims.
Claims
1. A high temperature resistant and anti-corrosion electrode slurry, characterized in that: According to the mass percentage, it includes: 45-77% Ag / Pd powder, 3-15% glass ceramic phase powder, and 15-20% organic carrier; wherein the glass ceramic phase powder is Al-Sm-Si-Ca-Mg system high temperature resistant glass powder; The glass ceramic phase powder includes, by mass percentage, one or more of: Al2O3 20-45%, MgO 15-25%, SiO2 10-15%, CaO 5-15%, ZnO 1-5%, Na2O / BeO 0.5-3%, Y2O3 0.5-5%, Sm2O3 / SrO 5-10%, MgF / ZrO2 0.5-5%, mullite powder 0.1-05%, and / or La2O3 0-2%, BeO 0-2%, BaO 0-2%, MnO2 0-2%, CuO 0-2%, K2O 0-2%, V2O5 0-2%, Li2O 0-2% / Gd2O3 0-2%.
2. The high temperature resistant and anti-corrosion electrode slurry according to claim 1, characterized in that: The mass ratio of MgF to ZrO2 in the MgF / ZrO2 is 3:7, the mass ratio of Na2O to BeO in Na2O / BeO is 2:1, and the mass ratio of Sm2O3 to SrO in Sm2O3 / SrO is 1:
4.
3. The method for preparing the high temperature resistant and anti-corrosion electrode slurry according to any one of claims 1-2, characterized in that: include: Step 1: Weigh the components of the glass ceramic phase powder according to mass percentage and mix them evenly; In terms of mass percentage, it includes: Al2O3 20-45%, MgO 15-25%, SiO2 10-15%, CaO 5-15%, ZnO 1-5%, Na2O / BeO 0.5-3%, Y2O3 0.5-5%, Sm2O3 / SrO 5-10%, MgF / ZrO2 0.5-5%, mullite powder 0.1-05%, and / or La2O3 0-2%, BeO 0-2%, BaO 0-2%, MnO2 0-2%, CuO 0-2%, K2O 0-2%, V2O5 0-2%, Li2O 0-2% / Gd2O3 0-2%; Step 2: Melting the uniformly mixed glass ceramic phase powder to obtain melted glass liquid; Step 3: The molten glass liquid is taken out, and subjected to water quenching, drying, ball milling, and sieving in sequence to obtain Al-Sm-Si-Ca-Mg system high temperature resistant glass powder; Step 4: Mix the Al-Sm-Si-Ca-Mg system high temperature resistant glass powder with Ag / Pd powder and an organic carrier to obtain a high temperature resistant and corrosion resistant electrode slurry, wherein the organic carrier includes a binder, a solvent and a dispersant.
4. The method for preparing the high temperature resistant and anti-corrosion electrode slurry according to claim 3, characterized in that: The melting in step 2 includes: heating the uniformly mixed glass-ceramic phase powder to 260-360°C at a heating rate of 2°C / min and keeping it warm for 0.5-2 hours, then heating it to 1400-1650°C at a heating rate of 3-5°C / min and keeping it warm for 1-2.5 hours to fully melt the glass and obtain melted glass liquid.
5. The method for preparing the high temperature resistant and anti-corrosion electrode slurry according to claim 3, characterized in that: In step 4, the mixing is performed by ball milling, agate balls are selected as grinding media, and the solid content of the mixture is 50-70%.
6. The method for preparing the high temperature resistant and anti-corrosion electrode slurry according to claim 3, characterized in that: In step 4, the binder is one or more of epoxy resin, silicone epoxy resin, and polyacrylate, and the solvent is one or more of dimethyl phthalate and terpineol; The dispersant is selected from one or both of methyl pyrrolidone and butanediol.